Bimetallic CoNiSx nanocrystallites embedded in nitrogen-doped carbon anchored on reduced graphene oxide for high-performance supercapacitors. Issue 8 (12th February 2018) - Chen, Qidi; Miao, Jinkang; Quan, Liang; Cai, Daoping; Zhan, Hongbing
Abstract : An unique rGO/CoNiS x /N–C nanocomposite has been successfully designed and synthesized by a simple one-step carbonization/sulfurization treatment of the rGO/Co–Ni precursor. Abstract : Exploring high-performance and low-priced electrode materials for supercapacitors is important but remains challenging. In this work, a unique sandwich-like nanocomposite of reduced graphene oxide (rGO)-supported N-doped carbon embedded with ultrasmall CoNiS x nanocrystallites (rGO/CoNiS x /N–C nanocomposite) has been successfully designed and synthesized by a simple one-step carbonization/sulfurization treatment of the rGO/Co–Ni precursor. The intriguing structural/compositional/morphological advantages endow the as-synthesized rGO/CoNiS x /N–C nanocomposite with excellent electrochemical performance as an advanced electrode material for supercapacitors. Compared with the other two rGO/CoNiO x and rGO/CoNiS x nanocomposites, the rGO/CoNiS x /N–C nanocomposite exhibits much enhanced performance, including a high specific capacitance (1028.2 F g −1 at 1 A g −1 ), excellent rate capability (89.3% capacitance retention at 10 A g −1 ) and good cycling stability (93.6% capacitance retention over 2000 cycles). In addition, an asymmetric supercapacitor (ASC) device based on the rGO/CoNiS x /N–C nanocomposite as the cathode and activated carbon (AC) as the anode is also fabricated, which can deliver a high energy density of 32.9 W h kg −1 at a power density of 229.2 W kg −1 with desirable cycling stability. These electrochemical results evidently indicate the great potential of the sandwich-like rGO/CoNiS x /N–C nanocomposite for applications in high-performance supercapacitors.